x → 0 lim x 2 1 − k = 1 ∏ 1 0 0 cos k x = ?
Bonus: Generalize for n or x → 0 lim x 2 1 − ∏ k = 1 n cos k x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Exactly the same!! L' Hopital is tedious here...!!
Log in to reply
Applying L'Hopital actually makes the problem easier.
Log in to reply
@Sravanth Chebrolu Well yeah, you can say that but I find manipulating polynomials much easier.......Also, differentiating a large product gives me bad vibes......lol.......personal preferences......!!
Log in to reply
@Aaghaz Mahajan – Oh, haha. I was just upset that I misclicked "discuss solutions". Btw, are you related to Nihar Mahajan?
Log in to reply
@Sravanth C. – @Sravanth Chebrolu No man!! But I do solve his problems and they are AMAZING!!!! Why so?? The surname??!! Which class are you in??
Log in to reply
@Aaghaz Mahajan – Yeah, the surnames match, so I asked. I'm in 12th Grade now. What about you?
Log in to reply
@Sravanth C. – Ohh I see......Preparing for JEE then...!! I have entered class 11th...!! Trying to up my Physics.....lol......I srsly can't understand ROTATION!!!! And that is only what is left in my mechanics section......!!
Log in to reply
@Aaghaz Mahajan – Oh nice, good luck for your future! Yep, preparing for advanced now 3 days left ...
Log in to reply
@Sravanth C. – Oh Acha!! That's osm!! So you are giving Advance....!! Congrats!! I thought that you had entered 12th...lol....Best of Luck!! And what was your AIR??
Log in to reply
@Aaghaz Mahajan – It was bad, I screwed up. I got 5017 AIR.
I clicked the view solution button by mistake, but applying L'Hopital make it very easy. Differentiating both numerator and denominator x → 0 lim 2 x sin x ( cos 2 x cos 3 x ⋯ cos 1 0 0 x ) + 2 x 2 sin 2 x ( cos x cos 3 x ⋯ cos 1 0 0 x ) + 2 x 3 sin 3 x ( cos x cos 2 x ⋯ cos 1 0 0 x ) ⋯
Now just apply, lim x → 0 x sin x = 1 we get: 2 1 2 + 2 2 2 + 2 3 2 ⋯ + 2 1 0 0 2 = 1 6 9 1 7 5
Relevant wiki: L'Hopital's Rule - Basic
Let f ( x ) = k = 1 ∏ n cos k x
lo g ( f ( x ) ) f ( x ) 1 ⋅ f ′ ( x ) f ′ ( x ) f ′ ′ ( x ) = k = 1 ∑ n lo g ( cos k x ) differentiate w.r.t x on both sides = k = 1 ∑ n cos ( k x ) 1 ⋅ − ( sin ( k x ) ) ⋅ k = − f ( x ) k = 1 ∑ n k tan ( k x ) = − f ′ ( x ) k = 1 ∑ n k tan ( k x ) − f ( x ) k = 1 ∑ n k 2 sec 2 ( k x )
Now , L = x → 0 lim x 2 1 − f ( x ) = x → 0 lim 2 x − f ′ ( x ) = x → 0 lim 2 − f ′ ′ ( x ) = 2 − f ′ ′ ( 0 )
f ′ ′ ( 0 ) = 0 − 1 ⋅ k = 1 ∑ n k 2 ⋅ 1 = − 6 n ( n + 1 ) ( 2 n + 1 )
L = 1 2 n ( n + 1 ) ( 2 n + 1 )
Yes. great solution . What I purely expected
This problem is already posted here L'Hopital Isn't The Saviour This Time!
Log in to reply
Not this one brother. It has 23 and here it is 100
Log in to reply
Yeah, the same approach. Just different values. :-)
Amar problem tar values change kore jhepe dili bol? xD
Log in to reply
@Arkajyoti Banerjee – Tomar kothay dada.. Eta Ekta Competitive Exam er. :P
Jai e hok.
Ha
Log in to reply
@Md Zuhair – Ha, idea ta okhan thekei peyechilam. The actual question was x → 0 lim ( sin x ) 2 1 − cos x cos 2 x cos 3 x
Tao dekh, ami question er dhoron tai change korechi, just not the values. Tuio ei question ta ke ektu modify korte partis arki, setai bolchi.
Ar "dada" bolar ki hoyeche? Tuio 16 amio 16. Tui just 10th e ar ami 11th e. Age ta same.
Log in to reply
@Arkajyoti Banerjee – Amar toh just ei kichu din agei 16 holo.. Tomar kobe hoyeche? Amar EI December e holo
Log in to reply
@Md Zuhair – Amar June e, but I don't think 6 months is enough for calling someone "dada" xD
Log in to reply
@Arkajyoti Banerjee – Haha... Half Dada :P
Log in to reply
@Md Zuhair – Lol exams kemon jacche? Maths e full marks pachhis toh?
Log in to reply
@Arkajyoti Banerjee – Maths ajj chilo,
Ajj Exams Sesh
Tai sara din Brilliant Korchi..
And Maths e jani na.. Bhaloi Hoyeche
Relevant wiki: L'Hopital's Rule - Basic
L n = x → 0 lim x 2 1 − ∏ k = 1 n cos k x = x → 0 lim 2 x ∏ k = 1 n cos k x ∑ j = 1 n j tan j x = x → 0 lim 2 − ∏ k = 1 n cos k x ( ∑ j = 1 n j tan j x ) 2 + ∏ k = 1 n cos k x ∑ j = 1 n j 2 sec 2 j x = 2 ∑ j = 1 n j 2 = 1 2 n ( n + 1 ) ( 2 n + 1 ) A 0/0 case, L’H o ˆ pital’s rule applies. Differentiate up and down; 0/0 case again. Differentiate up and down w.r.t. x again.
Therefore, for n = 1 0 0 , L 1 0 0 = 1 2 1 0 0 ( 1 0 1 ) ( 2 0 1 ) = 1 6 9 1 7 5 .
Note:
f ( x ) d x d f ( x ) = k = 1 ∏ n cos k x = cos ( x ) cos ( 2 x ) cos ( 3 x ) ⋯ cos ( n x ) = sin ( x ) k = 1 ∏ n cos k x + 2 sin ( 2 x ) k = 2 ∏ n cos k x + ⋯ + n sin ( n x ) k = n ∏ n cos k x = cos ( x ) sin ( x ) k = 1 ∏ n cos k x + cos ( 2 x ) 2 sin ( 2 x ) k = 1 ∏ n cos k x + ⋯ + cos ( n x ) n sin ( n x ) k = 1 ∏ n cos k x = k = 1 ∏ n cos k x j = 1 ∑ n j tan j k
Problem Loading...
Note Loading...
Set Loading...
A slightly different solution...
When x goes to 0, c o s ( k x ) goes to 1 − 2 ( k x ) 2 . It is important to write the x 2 term, since it appears on the denominator. So:
= x → 0 lim x 2 1 − ∏ k = 1 n ( 1 − 2 ( k x ) 2 )
= x → 0 lim x 2 1 − ( 1 − ∑ k = 1 n 2 ( k x ) 2 + O ( x 4 ) )
Since the terms x k , k > 2 goes to 0 faster than x 2 for x → 0 , we're looking only for the x 2 terms in the product. So:
= x → 0 lim x 2 1 − ( 1 − ∑ k = 1 n 2 ( k x ) 2 )
The x 2 goes outside the sum and cancels out with the denominator:
= 2 1 k = 1 ∑ n k 2
= 1 2 n ( n + 1 ) ( 2 n + 1 )
For n = 1 0 0 this is equal to 1 6 9 1 7 5